Piliakalnių tyrinėjimų kryptys Lietuvoje 1962–1987 metais - Zabiela, Gintautas (Archaeologia Lituana, 2008)
The history of Lithuanian soviet-period archaeology has not been written yet for several reasons. Among them one of the most important is a short time interval (less than a generation), causing the fact that for some Lithuanian archaeologists this history continues to represent the present. Yet, in this article I would like to discuss a rather narrow aspect of the history of Lithuanian soviet-period archaeology: Lithuanian hill-fort research trends in the period 1962–1987. This period has been chosen for the reason than from September 1, 1962 to May 29, 1987, the Archaeological Sector (Division since 1980) of the Lithuanian Institute of History was headed by Adolfas Tautavičius (1925–2006). In the totalitarian socialist system, the influence of an individual person entitled to manage the process was in fact decisive, and it was upon that person how far such influence and power were exercised. A. Tautavičius, although being a head of a department in an ideologically engaged institution (the Lithuanian Institute of History is to be considered as such), managed to avoid joining the Communist party. This enables us to raise a hypothesis about the “policy” of A. Tautavičius and its impact on the development of Lithuanian archaeology. The “policy” is to be written in quatation marks because neither the soviet regime nor the Lithuanian Institute of History itself encouraged heads of its departments to carry out an independent policy and especially to declare that officially. On the other hand, distinguishing the “policy” among other works of A. Tautavičius performed in the field of the archaeological science will help us to answer the question whether it existed at all.The sources of the study shall be based on the summation of the Lithuanian hill-fort researches performed at that period, covering the range from the excavation works to the synthetic hill-fort studies. The materials include both published and unpublished sources preserved in the written form (in the form of the research reports). Minutes of the Department meetings and scarce memoirs (as a bias source) were left out. The basis of the research sources had already been formed, because the most outstanding hill-fort researchers of that period already passed or retired.When A. Tautavičius overtook the management of the archaeological department, he inherited a considerable disproportion in the ratio of settlement researches and burial researches, which had formed from the very beginning of Lithuanian archaeology. He could not change that, yet the growth of the hill-fort research at the times of A. Tautavičius was the largest during the entire history of Lithuanian contemporary archaeology. Only 40 hill-forts had been investigated till 1963, yet in 1987 this number grew 2.5 times up to 106. These numbers alone can prove that A. Tautavičius considered hill-fort investigation as an important vector for the archaeological research. Hill-forts were out of specific interests of A. Tautavičius, so the development of hill-fort research was not relevant to his personal activities.The hill-fort research developed in two directions: excavation and registration. Implementation of the hill-fort research goals was rather complicated due to the scarcity of specialists. P. Kulikauskas and R. Kulikauskienė had a broad autonomy in this field, and at least in the first half of the A. Tautavičius’ management period they performed their researches following the earlier guidelines. Other archaeologists (A. Merkevičius, V. Daugudis) were still not ready to perform a continuous hill-fort research. Therefore, in the first half of A. Tautavičius’ period, the research concentrated on hill-fort registration. For this purpose, surveying expeditions started by P. Kulikauskas were continued. They were led by A. Tautavičius himself, and during the expeditions of 1963–1973 almost all Lithuanian hill-forts were surveyed. This work resulted in the Archaeological Atlas of Lithuanian SSR (Lietuvos TSR archeologijos atlasas, T. II, 1975). A. Tautavičius was an editor and a co-author of this volume. it covered 855 hill-forts divided into the following categories: unquestionable (600), assumable (200) and destroyed (50). The publication of this book completed the implementation of one of the hill-fort investigation tasks that A. Tautavičius used to set for Lithuanian archaeology.In the second half of A. Tautavičius’ period, the main feature of hill-fort research was its comprehensive character. For this purpose, a professional team of archaeologists specialising in hill-fort research was formed. Among them, Vytautas Daugudis (1929–2002) was the most outstanding figure. He had been doing hill-fort research since 1968 while at the Scientific-Methodical Council of the Preservation of Cultural Monuments, established at the Ministry of Culture of Lithuanian SSR. In 1972, V. Daugudis returned to the Institute of History and joined the local hill-fort research. In 1979 he started long-term excavations of the Imbarė hill-fort. Another outstanding archaeologist working in the field was Elena Grigalavičienė (1935–2005). Since 1964 she had been investigating brushed pottery and in 1976 started research of hill-forts attributable to Brushed Pottery Culture. R. Kulikauskienė and P. Kulikauskas carried out investigations of hill-forts in the most important Lithuanian centres. Meantime the younger generation of hill-fort researchers was raised as well.During this period, hill-fort research became better guided. Investigations of Brushed Pottery Culture, bone artefacts, hill-forts of Western Lithuania and hill-fort fortifications became the main subjects. It was attempted to research hill-forts in various locations of Lithuania, especially concentrating on the regions where no such research had been done before or were they were performed in the first half of the 20th century. The main result of these works was the 5th volume of Lithuanian Archaeology (Lietuvos archeologija, T. 5, 1986) publishing materials on three hill-forts of Brushed Pottery culture (Narkūnai, Nevieriškės, Sokiškiai) research performed in 1976–1983 and the book by V. Daugudis Senoji medinė statyba Lietuvoje (Ancient wooden buildings in Lithuania) published in 1982. A separate result of the hillfort research was the book by P. Kulikauskas Užnemunės piliakalniai I–XIII amžiuje (Hill-forts of the Nemunas left bank region in the 1st–13th centuries), published in 1982. By the end of this period, the accumulated results of hill-fort research gave an ideal mosaic view of Lithuanian hill-forts with a lot of details. Unfortunately, it was neither summarised nor published. Research of the Imbarė hill-fort probably presents one of the best examples of the case. In that period, only this kind of result was possible.Summarising the period when Lithuanian archaeology was led by A. Tautavičiaus, we can conclude, that he carried out a purposeful but an unhurried research policy aimed at collecting versatile data on hill-forts. Hill-fort research data accumulated during that period still serve as a basis for the present-day Lithuanian archaeology.